Police involvement in counter-terrorism and public attitudes towards the police in Israel 1998–2007 - Jonathan, Tal (The British journal of criminology, 2010)
Public attitudes towards the police are considered one of the important outcomes of policing in democratic countries. However, it is not clear how policing terrorism may affect these evaluations. The ‘Rally Effect' provides a context for examining this question, and suggests that when faced with severe terrorism threats, public perceptions of the police will rise in the short term but decline over time. Utilizing this framework, this article examines fluctuations in attitudes of Jewish adults in Israel towards the police over the past decade, within the context of legitimacy and procedural justice. The results lend support for the hypothesized model, and suggest that in addition to police conduct, public attitudes toward the police may be influenced by larger social forces